Cone penetration test calibration for Erksak (Beaufort Sea) sand - Been, K.; Lingnau, B. E.; Crooks, J. H. A.; Leach, B. (Canadian Geotechnical Journal, 1987)
Interpretation of the cone penetration test in sands is generally based on empirical calibrations from tests in large-diameter calibration chambers. Although interpretation of these calibration data for clean sands in terms of the state parameter is expected to be broadly applicable to other sands, material-specific correlations are desirable for many projects. This paper describes a series of calibration chamber tests carried out on a sand dredged from the Beaufort Sea for construction of artificial islands. This Erksak sand is a uniformly graded, subrounded medium-grained sand with a fines content of 3–6%. The testing chamber described is 1.4 m in diameter, and allows independent control of vertical, horizontal, and back pressures on the sand sample. Samples of the sand were prepared by moist compaction to preserve the fines content, and then back pressure saturated.The chamber test data are presented and confirm that the Erksak sand fits the general trends observed for other sands very well. A method is also described that allows the interpretation to be consistent, even in the event that nonuniform void ratios occur in the samples. Measurements of horizontal stress behind the cone tip, which is a new development in cone penetrometer testing, are also presented. Key words: cone penetrometer, sands, in situ tests, state, calibration chamber, horizontal stress measurement.